2017
DOI: 10.1021/acs.iecr.7b02182
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Large Aspect Ratio Ba0.85Ca0.15Zr0.1Ti0.9O3 Superfine Fibers-Based Flexible Nanogenerator Device: Synergistic Effect on Curie Temperature, Harvested Voltage, and Power

Abstract: Large aspect ratio Ba0.85Ca0.15Zr0.1Ti0.9O3 (BZCT) nanofibers mat was prepared using the electro-spinning technique. Crystal structure analysis confirmed the existence of MPB between tetragonal and rhombohedra phases. The morphology study suggested the formation of discrete nanofibers having a diameter 80–250 nm. Dielectric studies were performed on sintered nanofibers and Curie temperature (T C) was measured at ∼108 °C, which showed a significantly improved T C than that for bulk BCZT particles. The sintered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…However, the dielectric constant and the dielectric loss in BCZT ceramics with rod-like grains reached 11,906 and 0.014, respectively. Hence, tailoring BCZT ceramics with large aspect ratio could enhance its dielectric properties [49,50].…”
Section: Dielectric and Ferroelectric Properties Of Rod-like Bczt Cmentioning
confidence: 99%
“…However, the dielectric constant and the dielectric loss in BCZT ceramics with rod-like grains reached 11,906 and 0.014, respectively. Hence, tailoring BCZT ceramics with large aspect ratio could enhance its dielectric properties [49,50].…”
Section: Dielectric and Ferroelectric Properties Of Rod-like Bczt Cmentioning
confidence: 99%
“…Other perovskite structures such as Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 (d 33 ¼ 400-600 pC N À1 ), [112] Ba 0.85 Zr 0.1 Ti 0.9 O 3 (d 33 ¼ 185 pC N À1 ), [113,114] Y 2 O 3 ÀBa(Ti 0.96 Sn 0.04 )O 3 (d 33 ¼ 454 pC N À1 ), [115] and (Na 0.82 K 0.18 ) 0.5 Bi 0.5 TiO 3 (125À157 pm V À1 ) [116] have rarely been used to convert mechanical energy to electricity. Among ferroelectric materials, alkaline niobates such as (K, Na)NbO 3 have been considered as a desirable alternate for lead-free piezoelectric devices due to their high piezoelectricity, high Curie temperature (T C ¼ 415 C), large dielectric constant, and electromechanical coupling.…”
Section: Other Pngs Based On Perovskite Micro-/nanostructuresmentioning
confidence: 99%
“…38 It was stated that the electrical properties and the energy storage performances are highly affected by the shape of the ferroelectric material, hence, many works have attempted to elaborate BCZT ceramics with different morphologies namely nanowires and nanofibers. [39][40][41][42][43] Zhou et al prepared BCZT nanowires (BCZT-NWs) via two-steps hydrothermal processing and found that the peak power density could be enhanced 9 times by using BCZT-NWs instead of BCZT nanoparticles. 44 In the present study, BCZT with more complex nanostructures was elaborated through sol-gel followed by twosteps hydrothermal processes.…”
Section: -29mentioning
confidence: 99%